Dynamic behaviors and protection mechanisms of sulcata tortoise carapace. Issue 13 (3rd October 2021) - Jearanaisilawong, P.; Jongpairojcosit, N.; Glunrawd, C.
Abstract: This paper presents the compressive behavior of tortoise carapace at high strain rates and its protection mechanisms under impact loading. Both experimental and numerical results are reported. Tortoise is a land-based desert-dwelling animal taxonomically classified in the order of Testudines. The carapace is the dome-shaped upper part of the tortoise shell that protects its body from predator attacks. The carapace structure is composed of four layers formed as a composite structure with a porous core. The outer surface is keratin scutes made of fibrous structural proteins. The remaining layers are bone-like materials which are dorsal cortex, cancellous interior and ventral cortex. The compressive behavior at high rate of deformation is examined using split Hopkinson pressure bar (SHPB) technique. The results shown in the stress-strain plot illustrate a strain-rate hardening effect. The impact test is conducted using a gas gun with 6.35-mm diameter steel bearing balls as projectiles. The responses of carapace sample under a range of impact velocities are investigated to analyze its protection mechanisms. The numerical model of impact test is created to obtain an insight into mechanical behaviors of the carapace structure that cannot be observed in the experiments. The strain rate dependent material model is defined based on the SHPB test results. The distributions of stress and rebound velocity are presented and discussed.